Academic and social challenges faced by undergraduate EFL students in a non-English-speaking country: Lesson learned from the Indonesian International Students Mobility Awards (IISMA) program - Nurfitriana, Latifah; Ping, Maria Teodora; Asih, Yuni Utami (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Many studies have discussed the challenges faced by international students in English-speaking countries, but little focus on the academic and social challenges in non-English-speaking countries. This study aims to investigate the academic and social challenges faced by undergraduate EFL students in a non-English-speaking country during the Indonesian International Students Mobility Awards (IISMA) program. This case study involved two participants of undergraduate Indonesian students purposively selected from the IISMA program at a state-partnered university in Olomouc, Czech Republic. The data were collected through interviews and reflective journals, and they were analyzed deductively using thematic analysis. The findings show that students have substantial challenges due to the requirement to understand varied English accents and the lack of a shared native language in the IISMA program. However, the students enhanced their English skills by interacting with local people and experiencing social and academic challenges. Despite these limitations, the use of supportive teaching methods and peer interactions enhances students' English proficiency and overall academic experience, even in non-English-speaking contexts like the Czech Republic. This suggests that such approaches could be widely applicable in similar educational environments, offering potential insights for improving language education